Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the value of [tex]\( x^3 + \frac{1}{x^3} \)[/tex] given that [tex]\( x - \frac{1}{x} = \frac{1}{6} \)[/tex], we can use some algebraic identities and manipulation.
1. Let's denote [tex]\( y \)[/tex] as [tex]\( x - \frac{1}{x} \)[/tex]:
[tex]\[ y = \frac{1}{6} \][/tex]
2. We need to find [tex]\( x^3 + \frac{1}{x^3} \)[/tex]. To do this, we use the identity:
[tex]\[ (x - \frac{1}{x})^3 = x^3 - 3x + 3 \cdot \frac{1}{x} - \frac{1}{x^3} \][/tex]
Simplifying, we get:
[tex]\[ (x - \frac{1}{x})^3 = x^3 + \frac{1}{x^3} - 3(x - \frac{1}{x}) \][/tex]
3. Substituting [tex]\( y \)[/tex] and [tex]\( y^3 \)[/tex] into this identity, we obtain:
[tex]\[ y^3 = x^3 + \frac{1}{x^3} - 3y \][/tex]
4. Since [tex]\( y = \frac{1}{6} \)[/tex], we can calculate [tex]\( y^3 \)[/tex]:
[tex]\[ y^3 = \left( \frac{1}{6} \right)^3 = \frac{1}{216} \][/tex]
5. Now, substitute [tex]\( y \)[/tex] and [tex]\( y^3 \)[/tex] back into the equation:
[tex]\[ \frac{1}{216} = x^3 + \frac{1}{x^3} - 3 \cdot \frac{1}{6} \][/tex]
6. Calculate [tex]\( 3 \cdot \frac{1}{6} \)[/tex]:
[tex]\[ 3 \cdot \frac{1}{6} = \frac{1}{2} \][/tex]
7. Rearrange the equation to solve for [tex]\( x^3 + \frac{1}{x^3} \)[/tex]:
[tex]\[ \frac{1}{216} + \frac{1}{2} = x^3 + \frac{1}{x^3} \][/tex]
8. Simplify the right-hand side:
[tex]\[ \frac{1}{2} = 0.5 \quad \text{and} \quad \frac{1}{216} = 0.00462962962962963 \][/tex]
9. Adding these values together:
[tex]\[ x^3 + \frac{1}{x^3} = 0.5 + 0.00462962962962963 = 0.5046296296296297 \][/tex]
Thus, the value of [tex]\( x^3 + \frac{1}{x^3} \)[/tex] is:
[tex]\[ \boxed{0.5046296296296297} \][/tex]
1. Let's denote [tex]\( y \)[/tex] as [tex]\( x - \frac{1}{x} \)[/tex]:
[tex]\[ y = \frac{1}{6} \][/tex]
2. We need to find [tex]\( x^3 + \frac{1}{x^3} \)[/tex]. To do this, we use the identity:
[tex]\[ (x - \frac{1}{x})^3 = x^3 - 3x + 3 \cdot \frac{1}{x} - \frac{1}{x^3} \][/tex]
Simplifying, we get:
[tex]\[ (x - \frac{1}{x})^3 = x^3 + \frac{1}{x^3} - 3(x - \frac{1}{x}) \][/tex]
3. Substituting [tex]\( y \)[/tex] and [tex]\( y^3 \)[/tex] into this identity, we obtain:
[tex]\[ y^3 = x^3 + \frac{1}{x^3} - 3y \][/tex]
4. Since [tex]\( y = \frac{1}{6} \)[/tex], we can calculate [tex]\( y^3 \)[/tex]:
[tex]\[ y^3 = \left( \frac{1}{6} \right)^3 = \frac{1}{216} \][/tex]
5. Now, substitute [tex]\( y \)[/tex] and [tex]\( y^3 \)[/tex] back into the equation:
[tex]\[ \frac{1}{216} = x^3 + \frac{1}{x^3} - 3 \cdot \frac{1}{6} \][/tex]
6. Calculate [tex]\( 3 \cdot \frac{1}{6} \)[/tex]:
[tex]\[ 3 \cdot \frac{1}{6} = \frac{1}{2} \][/tex]
7. Rearrange the equation to solve for [tex]\( x^3 + \frac{1}{x^3} \)[/tex]:
[tex]\[ \frac{1}{216} + \frac{1}{2} = x^3 + \frac{1}{x^3} \][/tex]
8. Simplify the right-hand side:
[tex]\[ \frac{1}{2} = 0.5 \quad \text{and} \quad \frac{1}{216} = 0.00462962962962963 \][/tex]
9. Adding these values together:
[tex]\[ x^3 + \frac{1}{x^3} = 0.5 + 0.00462962962962963 = 0.5046296296296297 \][/tex]
Thus, the value of [tex]\( x^3 + \frac{1}{x^3} \)[/tex] is:
[tex]\[ \boxed{0.5046296296296297} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.